2000
DOI: 10.1021/ar970209q
|View full text |Cite
|
Sign up to set email alerts
|

Metal Ion Effects in Isotopic Hydrogen Exchange in Biologically Important Heterocycles

Abstract: The binding of metal ions to heteroatomic centers of biomolecules has been utilized as a probe of metal ion effects in living systems. This article focuses on the effect of N-coordination by transition metals, especially Pt(II), Co(III), Cr(III), on isotopic C(2)-H or C(8)-H exchange of imidazoles, thiazoles, and purines. The usual reactivity trend, protonated >> metalated >> neutral substrate, is excepted for Cr(III)/1-methylimidazole, where Cr(III) activates stronger than H(+). An interplay of factors is con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 42 publications
1
12
0
Order By: Relevance
“…This study expands upon our previous work, presenting evidence for another class of strong carbon donor hydrogen bonds in proteins, those donated by imidazole side chains complexed to metals. This is consistent with measured isotopic proton-exchange rates at C-H sites of imidazole, which are enhanced by protonation or metal binding [13,14]. Histidine is a frequent metal ligand in proteins [15], and the importance of metal-activated imidazoles to protein stability and function is worth further examination.…”
Section: Introductionsupporting
confidence: 82%
See 1 more Smart Citation
“…This study expands upon our previous work, presenting evidence for another class of strong carbon donor hydrogen bonds in proteins, those donated by imidazole side chains complexed to metals. This is consistent with measured isotopic proton-exchange rates at C-H sites of imidazole, which are enhanced by protonation or metal binding [13,14]. Histidine is a frequent metal ligand in proteins [15], and the importance of metal-activated imidazoles to protein stability and function is worth further examination.…”
Section: Introductionsupporting
confidence: 82%
“…Later, we compare the strength of these two carbon donors using models of the SOR active site. Previous calculations for neutral and charged imidazole [11,12] and experimentally measured exchange rates in imidazole-metal complexes [13,14] would suggest that interactions at Ce 1 are stronger than at Cd 2 .…”
Section: Comparisons Of Isolated Imidazole To Metal Complexed Imidazolementioning
confidence: 93%
“…The deuterium-hydrogen exchange can be analysed as a pseudo-first order process. The kinetics parameter k i (first-order rate constant) of the DHX reaction can be determined as A recent paper 51,52 has demonstrated that binding of metal ions influences the hydrogen-deuterium exchange of the imidazole ring C2-hydrogen in histidine-containing peptides. The k values for the peptide at pH 5.2 and its complex at pH 5.2, 7.2, 7.3, 8.2, and 8.3 are equal to 0 within experimental error limits.…”
Section: Resultsmentioning
confidence: 99%
“…2 (+)-Echinobetaine B (6) is a new example of a rare class of naturally occurring imidazole betaine. The first example of this structure class was zooanemonin (12) reported by Ackermann and Menssen in 1960 from the "horse sponge", Hippospongia equina. 7 Although the structure of 12 was revised shortly thereafter (following communication on its synthesis by Woodward and List), 8 few subsequent references have appeared in the scientific literature.…”
Section: Resultsmentioning
confidence: 99%